RELATIONSHIP OF MEDICAL RECORD SERVICES TO OUTPATIENT SATISFACTION AT GRANDMED LUBUK PAKAM HOSPITAL - Felix Kasim; Ruth Diah Ayuni Sihaloho (JURNAL KESMAS DAN GIZI (JKG), 2022)
Patients as users of health services demand services provided in accordance with their rights, namely quality and perfect services. Patients expect officers to provide services that match their interests and expectations, namely humane, responsive, empathetic, friendly and communicative. This study is a quantitative study with a cross sectional research design which aims to determine the relationship between medical record services and patient satisfaction at the Grandmed Lubuk Pakam hospital. The sample in this study was taken using accidental sampling technique of 33 respondents. Data was collected using a questionnaire and tested using the chi square test. The results showed that the medical record service at Grandmed Lubuk Pakam Hospital was in the good category (54.5%), most of the patients said they were satisfied with the medical record service (66.7%) and statistically there was a relationship between medical record service and patient satisfaction at the hospital. Grandmed Lubuk Pakam (p=0.009).